Sudden Onset, Fixed Dystonia and Acute Peripheral Trauma as Diagnostic Clues for Functional Dystonia. Issue 7 (10th September 2021) - Ercoli, Tommaso; Defazio, Giovanni; Geroin, Christian; Marcuzzo, Enrico; Fabbrini, Giovanni; Bono, Francesco; Mechelli, Alessandro; Ceravolo, Roberto; Romito, Luigi Michele; Albanese, Alberto; Pisani, Antonio; Zibetti, Maurizio; et al.
ABSTRACT: Background: The differentiation of functional dystonia from idiopathic dystonia may be clinically challenging. Objective: To identify clinical features suggestive of functional dystonia to guide physicians to distinguish functional dystonia from idiopathic dystonia. Methods: Patient data were extracted from the Italian Registry of Functional Motor Disorders and the Italian Registry of Adult Dystonia. Patients with functional and idiopathic dystonia were followed up at the same clinical sites, and they were similar in age and sex. Results: We identified 113 patients with functional dystonia and 125 with idiopathic dystonia. Sudden onset of dystonia, evidence of fixed dystonia, and acute peripheral trauma before dystonia onset were more frequent in the functional dystonia group. No study variable alone achieved satisfactory sensitivity and specificity, whereas a combination of variables yielded 85% sensitivity and 98% specificity. A diagnostic algorithm was developed to reduce the risk of misclassifying functional dystonia. Conclusion: Our findings extend the current diagnostic approach to functional dystonia by showing that clinical information about symptom onset, fixed dystonia, and history of peripheral trauma may provide key clues in the diagnosis of functional dystonia.